CHRONIC ENDOMETRITIS: CURRENT ASPECTS - V. E. RADZINSKY; Yu. A. PETROV; M. L. PОLINA (Кубанский научный медицинский вестник, 2017)
Aim. To broaden the understanding of chronic endometritis (CE) pathogenesis on the basis of the reception study of steroid hormones and markers of cell proliferation/apoptosis in its different types depending on the nature of microbial colonization of the uterine mucosa.Materials and methods. A group of 345 patients with early reproductive losses (non-developing pregnancy, spontaneous abortion, artificial abortion, in vitro fertilization (IVF) failure for up to 6 months after intrauterine intervention) who had histologically revealed chronic endometritis was prospectively examined. The following studies were performed: microbiological (PCR diagnostics, bacteriological examination of the cervical canal, mucous uterus); instrumental (hysteroscopy). Vacuum suction biopsy of the endometrium was performed on the 7th-9th days of the menstrual cycle (m.c.) during hysteroscopy and on the 22nd-24th days of the m.c. with the purpose of clarifying the condition of the mucosa, including pathomorphological examination. CE verification was carried out with macrotypes identification (hysteroscopic evaluation of mucosal thickness, in the dynamics of the cycle, and its color – the presence of hyperemia or pallor, focal or diffuse hyperemia, micropolyps, vascular responses): hyper-, hypoplastic and mixed. Immunohistochemical study of the endometrium included evaluation of the expression of estrogens and progesterone receptors (Dako, Denmark), marker of mucosal proliferation (Ki-67) and apoptosis (CPP32).Results. Inflamed mucous uterus remodelling is realized in pathomorphosis and homoeokinesis characteristics of each macro-type caused by the variability of the balance of the processes of cell proliferation and apoptosis. The morphological basis of the hyperplastic macrotype is dystrophic-atrophic changes of the endometrium, mixed type reveals alternation of sites of dystrophy and fibrosis, hyperplastic – induction of micro-polypoid growths on the background of a lymphocytic infiltration of the mucosa. The rate of uterine mucosa cellular renewal in CE cases is detected by the activity of persistent infections in the endometrium: with endometrial dystrophy – the diagnostic titers of opportunistic strains (Escherichia coli, enterococcus, anaerobes, bacteroides), with mucosal mosaicism – mycoplasmas and their associations with HSV2 and opportunistic strains, with hyperplastic macrotypes – chlamydia, HSV2 and their combinations.Conclusion. The study of signalling chain markers of control over proliferative cascades at the endometrial level in comparison with the response to the introduction of a pathogenic infection and morphological transformations promotes the expansion of the concept of pathogenetic CE variants, and therefore, the choice of differentiated therapy for the purpose of restoring the fertile potential after reproductive losses.